Insights on the antifungal activity of amphiphilic derivatives of diethylaminoethyl chitosan against Aspergillus flavus - Dias, Amanda Manchini [UNESP]; dos Santos Cabrera, Marcia Perez [UNESP]; Lima, Aline Margarete Furuyama [UNESP]; Taboga, Sebastião Roberto [UNESP]; Vilamaior, Patricia Simone Leite [UNESP]; Tiera, Marcio José [UNESP]; de Oliveira Tiera, Vera Aparecida [UNESP] (Elsevier, 2018)
In this study, the antifungal activity of chitosan derivatives against A. flavus was studied to understand the contribution of the molecular mass (Mw) and of the hydrophobic and electrostatic forces to the inhibition of fungal growth. The interaction of amphiphilics ranging from 8 to 130 kDa with model membranes of zwitterionic L-α-phosphatidylcholine (PC) and anionic L-α-phosphatidylcholine/L-α-phosphatidyl-DL-glycerol (PC:PG, 80:20 mol%) were exploited to obtain information on the inhibition mechanism. The results indicated that concurrent interactions control the antifungal activity. The decrease in the Mw weakens the self-association favoring the electrostatic and hydrophobic associations with the cell wall and anionic lipids of the lipid bilayer, indicating an increasing association of the amphiphilics with the fungal membrane. Laser confocal scanning microscopy of rhodamine labeled-derivatives and transmission electronic microscopy techniques showed that the amphiphilics affect the cell wall integrity by inducing the aggregation of hydrophobic constituents of the conidia.
Keywords: Amphiphilic chitosan derivatives; Antifungal; Aspergillus flavus; Cell wall impairment; Inhibition